Performance Evaluation of a Solar-Assisted Multistage Heat Pump Drying System Based on the Optimal Drying Conditions for Solanum lycopersicum L. - Yimin Tang; Xiaoqiong Li; Peng Xu; Junling Yang; Zhentao Zhang; Ruixiang Wang; Dandan Zhao; Ramadan Elgamal (Foods)
This study aims to evaluate the drying performance of a multi-stage solar-assisted heat pump drying system for tomatoes. The method involves theoretical calculations based on the optimal drying process and experimental investigations to assess the impact of different drying temperatures and relative humidity on drying characteristics. The results from the theoretical calculations reveal that the multi-stage solar-assisted heat pump drying system outperforms a single-stage system, particularly under lower ambient temperatures or higher fresh air volumes. In spring/autumn, with 25% fresh air, solar energy accounts for 85.12% of the total energy consumption, achieving a performance coefficient of 39.16, a moisture extraction rate of 40.7 kg/kWh, and energy consumption of 0.02 kWh/kg. Carbon dioxide emissions amount to 10.45 kg/year, with a net reduction of 7.88 kg/year. The experimental results indicate that higher relative humidity increases drying time and reduces the diffusion coefficient, which results in higher material temperatures and greater nutrient loss. The optimal drying process is achieved at 70 °C and 20% relative humidity. In conclusion, the multi-stage solar-assisted heat pump drying system demonstrates superior performance in energy efficiency and sustainability compared to single-stage systems. The optimal drying conditions for tomatoes are identified, and the findings contribute to improving drying processes in food preservation while minimizing environmental impact.